Language of Instruction and Identity - chenane, Kouider (El Omda in Linguistics and Discourse Analysis, 2018)
The language of education and identity the identity of any nation sets the main features of the educational process and defines the basic features, cultural goals and socialization. Thus, the nature of education is the reflection of the identity of society. If we recognize this perception What is the role of education in ensuring, preserving and protecting identity? - Doesn’t the interest in the language of education works to chang the identity of the nation or abolish it ? These are Perhaps some of the social issues that are demolish in the silence the core of the nations and individuals .so, we will discuss these issues in this presentation, because they have a great importance in our culture today.